1968
DOI: 10.1017/s0025315400019159
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Shell Shape in the Mussel Mytilus Edulis

Abstract: An attempt is made to explain the great variations in gross shell morphology noted in field populations of Mytilus edulis.In any one mussel population, variation in shell form can be attributed to differences in age, old mussels having proportionately heavier shells where width often exceeds shell height. This is invariably accompanied by down-turned, divergent umbones and varying degrees of incurvature of the ventral shell margin.Variations in the age structure of mussel populations from different habitats ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
150
2
12

Year Published

1976
1976
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(178 citation statements)
references
References 23 publications
14
150
2
12
Order By: Relevance
“…Whitsand, Cawsand, Maenporth, Porthmeor, Westward Ho) albeit at a relatively low level, even when compared to recently infested estuarine populations of mussels. Seed (1968) has shown that mussels from estuarine sites are considerably larger than mussels of the same age on open coast sites. The differences in infestation levels, therefore, between mussels from these two types of site may be associated with differences in host size.…”
Section: Resultsmentioning
confidence: 99%
“…Whitsand, Cawsand, Maenporth, Porthmeor, Westward Ho) albeit at a relatively low level, even when compared to recently infested estuarine populations of mussels. Seed (1968) has shown that mussels from estuarine sites are considerably larger than mussels of the same age on open coast sites. The differences in infestation levels, therefore, between mussels from these two types of site may be associated with differences in host size.…”
Section: Resultsmentioning
confidence: 99%
“…Bivalve shell size was measured as the maximum long axis from the umbo to the ventral margin of the shell, which represents the shell height (SH) in oysters (Carriker, 1996) but is commonly referred to as the shell length (SL) in mussels (Seed, 1968). Oysters, C. virginica (SH = 15-78 mm), were obtained from Bay Enterprises Ltd., Malagash, and mussels, M. edulis (SL = 16-45 mm), from Indian Point Marine Farms Ltd., Mahone Bay, NS, Canada in May 2007.…”
Section: Biological Materialsmentioning
confidence: 99%
“…On tidal coasts, duration of air exposure of intertidal mussel beds is considered to be one of the most crucial factors controlling mussel growth (e.g. Baird & Drinnan 1957;Faldborg et al 1994;McGrorty 1997) and may lead to considerable variations in size and shape between intertidal and subtidal M. edulis (Baird 1966;Seed 1968).…”
Section: Introductionmentioning
confidence: 99%